Divided We Work: A Review on Political Polarization in Modern Business Organizations - Levkov, Nikola; Kitanovikj, Bojan (Academy of Management, 2025)
Research tackling political polarization in business organizations remains fragmented and relatively scarce. To understand the relevance of political polarization in businesses and manage the negative impact of political division on organizational operations, interpersonal relations, and organizational harmony, this investigation analyzed the literature surrounding the phenomenon of political polarization and its implications on business organizations, synthesized the findings in a framework, suggested strategies for mitigating this polarization in the work environment, and underscored pathways for future research using an integrative review approach. After a structured and rigorous thematic analysis of data from the databases Web of Science, Scopus, EBSCO, and JSTOR and adhering to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, results point to a lack of coherent research streams and concise antecedents and outcomes, which are relevant for conflict management, as well as limited evidence on the effects of political division and limited study contexts. Future research may focus on specifying management-related research purposes, reexamining organizational constructs on individual, team, and unit levels, and extending investigations on performance-related themes